1984
DOI: 10.1080/01688638408401221
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of rapidly Vs. slowly growing intrinsic cerebral neoplasms

Abstract: Four groups of patients with intrinsic cerebral neoplasms were compared to determine the differential effect of neoplasm (rapidly vs. slowly growing) and lateralization of damage (right vs. left hemisphere) upon neuropsychological functioning. No prior study has had enough subjects with neoplastic lesions to permit this kind of investigation. The group with rapidly growing neoplasms consistently had greater neuropsychological impairment. Lateralization of cerebral damage was found to have a differential effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
4

Year Published

1986
1986
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 26 publications
2
33
1
4
Order By: Relevance
“…25,26 Additionally, by following patients longitudinally with structural imaging, patients with disease progression were identified and excluded from analysis with the RT nonprogressor individuals. Given the recognition that disease progression could have a negative impact upon cognitive functioning, 17,27 it was important to exclude progressors to evaluate pure RT effects in isolation and to avoid overestimating the negative effect attributed to RT.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Additionally, by following patients longitudinally with structural imaging, patients with disease progression were identified and excluded from analysis with the RT nonprogressor individuals. Given the recognition that disease progression could have a negative impact upon cognitive functioning, 17,27 it was important to exclude progressors to evaluate pure RT effects in isolation and to avoid overestimating the negative effect attributed to RT.…”
Section: Discussionmentioning
confidence: 99%
“…Rate of tumor growth is a predictor of cognitive impairment, as slow tumor growth is often associated with less severe cognitive dysfunction than rapid tumor growth [12]. Tumor type or volume has not been found to predict cognitive performance in adults with astrocytomas and glioblastomas [13].…”
Section: Tumor and Treatment Effects On Cognitionmentioning
confidence: 99%
“…Also, children with a shorter duration of symptoms prior to diagnosis showed a trend toward poorer outcome, presumably as a consequence of a more aggressive tumor. It has long been observed that lesions with greater "momentum" produce more dramatic symptoms (Jackson, 1880), a principle which has been found to apply in the case of adult brain-tumor patients (Hom & Reitan, 1984).…”
Section: Presenting Symptomsmentioning
confidence: 98%